HUBUNGAN LINGKAR LENGAN ATAS (LILA) DENGAN BERAT BADAN LAHIR BAYI DI WILAYAH KERJA PUSKESMAS SEI LANGKAI KOTA BATAM - Rona, Rona; Aryaneta, Yenni (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
In pregnancy globally that is equal to (35-75%). WHO also noted that (40%) maternal deaths in developing countries are related to chronic energy deficiency. Pregnant women who suffer from malnutrition such as chronic lack of energy have a greater risk of illness and therefore malnutrition in pregnant women should be avoided so that pregnant women are a target group that needs special attention. The countries that experienced the highest incidence of CED in pregnant women were Bangladesh (47%), while Indonesia was the fourth largest with prevalence (35.5%) and Thailand with the lowest prevalence (15–25%). The purpose of this study was to determine the relationship between Upper Arm Circumference (LILA) and Birth Weight of Babies in the Work Area of the Sei Langkai Health Center Batam City in 2020. This study was a Case Control (Retrospective) study, the research site was in the Sei Langkai Health Center Work Area Batam City from the month August-September 2020, the study population was mothers who were recorded to have given birth in the Work Area of the Sei Langkai Health Center, Batam City in June 2020. Sampling using the Total sampling technique, the number of samples was 61 respondents, the instrument used for the independent variable and the dependent variable was using a checklist. used is chi-square analysis. Bivariate results, from 61 respondents, the results obtained showed that respondents who had an Upper Arm Circumference (LILA) <23.5 cm as many as 4 respondents (6.6%) gave birth to babies with birth weight <2500 grams (LBW) 4 (6 ,6%). While respondents who have an Upper Arm Circumference (LILA) 23.5 cm as many as 57 (93.4%) gave birth to babies with a birth weight of 2500-4000 grams (Normal) 57 (93.4%). The results of the statistical test with Chi-Square obtained p value = 0.000 <0.05 it can be concluded that Ho is rejected, meaning that there is a Relationship between Upper Arm Circumference (LILA) and Infant Birth Weight in the Work Area of the Sei Langkai Health Center Batam City in 2020. Suggestions to It is hoped that the research location can improve the service system, especially in the MCH room and for health workers to provide better services such as reminding mothers to always meet their nutritional needs, especially during pregnancy so that mothers do not experience malnutrition which can cause chronic energy deficiency (KEK) and can affect growth and development of the fetus, causing the risk of giving birth to babies with low birth weight (LBW).